Report on the Research Results of the Centre for Regional Studies of the Hungarian Academy of Sciences - Horváth, Gyula (Discussion Papers, 2012)
The National Regional Development Council proposed to publish the report of the Centre for Regional Studies on research results that have been completed between years 1998-2001. This report includes a pragmatically arranged listing and descriptions of research works. This summary deliveres a scientific message to those who are interested in the present problems of Hungarian regional policy and practice. The researches that include international comparisons as well, acknowledge the competitiveness of Hungarian regional policy, which has been established by the past results of Hungarian regional development. At the same time they also warn that this competitive advantage may be lost if we are unable to take an active part in forming the future of European regional policy and remain unprepared for the new challenges. A great encouragement has been given to us from some scientific papers urging for a more decentralised, regionalised territorial development policy, which may both serve as remedy for all of our national problems and as a catalyst for in benefiting all the advantages that our EU membership provides for regional policy. From the point of our future tasks, researches have clearly proved that region-based national planning has vital importance in the future of Hungarian society and economy.